Effect of potential voltages on key functional properties of transparent AZO thin films prepared by electrochemical deposition method for optoelectronic applications. Issue 11 (12th June 2018) - Arun Kumar, Karuppiah Deva; Valanarasu, Santiyagu; Ganesh, Vanga; Shkir, Mohd.; AlFaify, Salem; Algarni, Hamed
Abstract: Abstract : The electrochemical technique has been used to prepare aluminum-doped zinc oxide (AZO) films on FTO substrates using zinc nitrate and aluminum chloride precursor solution at 70 °C. The crystal structure, surface morphology, optical and electrical features of AZO films were examined at different potential voltages from −1.7 to −2.3 V in the initial solution. Structural studies of the deposited films were carried out through X-ray diffraction; the AZO films exhibited a polycrystalline nature with hexagonal structure, and crystals preferentially grew along the (002) orientation. The morphology of the deposited films was characterized by scanning electron microscopy (SEM), and the images showed that the spherical- and nanorod-shaped particles are uniformly distributed on the entire AZO film surface. The average size is found to be in the range of 45–70 nm by SEM and 28–32 nm by using the Scherrer's rule. The EDS spectrum confirmed the chemical composition of Zn, O, Al, Sn, and F elements over the film surface. The optical properties were studied using a UV-visible spectrophotometer, and the deposited film showed the highest optical transmittance of ∼80% in the visible range for −1.7 V. The calculated energy gap of the AZO films decreases from 3.09 to 2.97 eV with increasing potential voltages. AZO thin films have been studied using photoluminescence to identify the film's optical quality with respect to the wavelength range. The electrical properties were studied by the room temperature Hall effect system, and the observed low resistivity (ρ) is 1.58 × 10 −2 (Ω cm) for the film deposited using a −2.1 V potential voltage.